Submarine lateglacial lake deposits from jutland bank, the north sea - Ole Bennike; Bent Odgaard; Peter Wiberg-Larsen; Niels Nørgaard-Pedersen (Quaternary International, 2023)

Pollen richness: a reflection of vegetation diversity or pollen-specific parameters? - Vivika Väli; Bent Vad Odgaard; Ülo Väli; Anneli Poska (Vegetation History and Archaeobotany, 2022)

Circumstantial evidence of non-pollen palynomorph palaeoecology: a 5,500 year NPP record from forest hollow sediments compared to pollen and macrofossil inferred palaeoenvironments - Renée Enevold; Peter Rasmussen; Mette Løvschal; Jesper Olsen; Bent Vad Odgaard (Vegetation History and Archaeobotany, 2019)

Late Holocene landscape development around a Roman Iron Age mass grave, Alken Enge, Denmark - Niels Emil Søe; Bent Vad Odgaard; Anne Birgitte Nielsen; Jesper Olsen; Søren M. Kristiansen (Vegetation History and Archaeobotany, 2017)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Climate-driven changes in water level: a decadal scale multi-proxy study recording the 8.2-ka event and ecosystem responses in Lake Sarup (Denmark) - Rikke Bjerring; Jesper Olsen; Erik Jeppesen; Bjørn Buchardt; Jan Heinemeier; Suzanne McGowan; Peter R. Leavitt; Renée Enevold; Bent V. Odgaard (Journal of Paleolimnology, 2013)

The role of cladocerans in tracking long-term change in shallow lake trophic status - Thomas A. Davidson; Helen Bennion; Erik Jeppesen; Gina H. Clarke; Carl D. Sayer; David Morley; Bent V. Odgaard; Peter Rasmussen; Ruth Rawcliffe; Jorge Salgado; Gavin L. Simpson; Susanne L. Amsinck (Hydrobiologia, 2011)

Quantitative landscape dynamics in Denmark through the last three millennia based on the Landscape Reconstruction Algorithm approach - Anne Birgitte Nielsen; Bent Vad Odgaard (Vegetation History and Archaeobotany, 2010)

Revised age estimate of the Mjáuvøtn tephra A on the Faroe Islands based on Bayesian modelling of 14 C dates from two lake sequences - Jesper Olsen; Esther Ruth Gudmundsdóttir; Svante Björck; Bent V. Odgaard; Jan Heinemeier (Journal of Quaternary Science, 2010)
Tephra horizons are potentially perfect time markers for dating and cross‐correlation among diverse Holocene palaeoenvironmental records such as ice cores and marine and terrestrial sequences, but we need to trust their age. Here we present a new age estimate of the Holocene Mjáuvøtn tephra A using accelerator mass spectrometry 14 C dates from two lakes on the Faroe Islands. With Bayesian age modelling it is dated to 6668–6533 cal. a BP (68.2% confidence interval) – significantly older and better constrained than the previous age. Copyright © 2010 John Wiley & Sons, Ltd.

The use of historical analogues for interpreting fossil pollen records - Anne Birgitte Nielsen; Bent Vad Odgaard (Vegetation History and Archaeobotany, 2004)

Fossil pollen as a record of past biodiversity - Bent Vad Odgaard (Journal of Biogeography, 1999)
Summary Quaternary pollen records may contribute uniquely to the understanding of present plant diversity. Pollen assemblages can reflect diversity at community and landscape scales but the time resolution of most studies does not match that of modern ecological studies. Because of the complicating effects of differential pollen productivity and dispersal, pollen records do not directly reflect equitability aspects of vegetation diversity. Vegetation diversity indices other than S (the total number of taxa) are therefore not appropriate for pollen assemblages. As a measure of the species richness palynological richness is biased by the lack of taxonomic precision, by a possible interference on pollen dispersal from vegetation structure and by pollen representation. The nonlinear relationship between species richness and pollen‐taxa richness may be used in attempts to estimate past floristic richness from fossil pollen assemblages. Using a hypothetical example the strong effect of cover shifts in the vegetation affecting taxa with different representation (R rel ) values on observed palynological richness is demonstrated. It is suggested that estimates of relative pollen productivity should be used to guide the pollen sum on which pollen‐type richness is estimated by rarefaction techniques and this approach is illustrated using a paired site study of late Holocene diversity dynamics. The need for a modern training set relating pollen‐type richness to species richness, pollen productivity and vegetation structure is emphasized.

Pollen-landscape relationships in modern analogues of ancient cultural landscapes in southern Sweden ? a first step towards quantification of vegetation openness in the past - Anna Brostrm; Marie-Jos Gaillard; Margaretha Ihse; Bent Odgaard (Vegetation History and Archaeobotany, 1998)